A Revised Modular Approach to (–)‐trans‐Δ8‐THC and Derivatives Through Late‐Stage Suzuki–Miyaura Cross‐Coupling Reactions. Issue 12 (18th March 2019) - Bloemendal, Victor R. L. J.; Sondag, Daan; Elferink, Hidde; Boltje, Thomas J.; van Hest, Jan. C. M.; Rutjes, Floris P. J. T.
Abstract : A revised modular approach to various synthetic (–)‐ trans ‐Δ 8 ‐THC derivatives through late‐stage Suzuki–Miyaura cross‐coupling reactions is disclosed. Ten derivatives were synthesized allowing both sp 2 ‐ and sp 3 ‐hybridized cross‐coupling partners with minimal β‐hydride elimination. Importantly, we demonstrate that a para ‐bromo‐substituted THC scaffold for Suzuki–Miyaura cross‐coupling reactions has been initially reported incorrectly in recent literature. Abstract : A revised modular approach to various synthetic (–)‐ trans ‐Δ 8 ‐THC derivatives is disclosed. Ten derivatives were sythesized using both sp 2 ‐ and sp 3 ‐hybridized fragment couplings.